1994
DOI: 10.1161/01.hyp.23.6.1063
|View full text |Cite
|
Sign up to set email alerts
|

Renal sensory receptor activation by calcitonin gene-related peptide.

Abstract: In anesthetized rats we examined whether calcitonin gene-related peptide activated renal pelvic sensory receptors and, if so, whether activation of renal pelvic calcitonin gene-related peptide receptors contributes to the inhibitory renorenal reflex response to renal mechanoreceptor stimulation. Calcitonin gene-related peptide (0.0026, 0.026, 0.26, and 2.6 ^imol/L) administered into the renal pelvis increased ipsilateral afferent renal nerve activity in a concentrationdependent fashion (32±14%, 69±19%, 93±26%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…CGRP was given at 0.026 mol/L in the first group (nϭ8) and at 0.26 mol/L in the second group (nϭ8), both concentrations being submaximum in activating renal sensory nerves. 7 Substance P was given at the submaximum concentration of 3.7 mol/L 3 in both groups.…”
Section: Effects Of Cgrp On Arna Response To Substance Pmentioning
confidence: 99%
See 4 more Smart Citations
“…CGRP was given at 0.026 mol/L in the first group (nϭ8) and at 0.26 mol/L in the second group (nϭ8), both concentrations being submaximum in activating renal sensory nerves. 7 Substance P was given at the submaximum concentration of 3.7 mol/L 3 in both groups.…”
Section: Effects Of Cgrp On Arna Response To Substance Pmentioning
confidence: 99%
“…Our previous studies have shown that the duration of the ARNA response to 0.26 mol/L CGRP is Ͻ60 seconds. 7 In the second group (time control, nϭ7), the experimental protocol was the same as in the first group except 0.15 mol/L NaCl was given into the renal pelvis instead of CGRP.…”
Section: Effects Of Cgrp On Arna Response To Increased Renal Pelvic Pmentioning
confidence: 99%
See 3 more Smart Citations